Comportamento à fadiga de materiais cerâmicos - Fraga, Sara (2016)
Two manuscripts about the fatigue behavior of ceramic materials are reported in this thesis. Manuscript 1: Impact of the CAD/CAM machining on the fatigue behavior of glass and polycrystalline ceramics. This study assessed the effect of CAD/CAM machining on the flexural fatigue strength and on the surface roughness of different ceramics by comparing machined vs. machined and polished specimens. Disc shaped specimens of Y-TZP, leucite- and lithium disilicate-based glass ceramics were prepared by CAD/CAM machining, and assigned into two groups: machining (M); and machining followed by polishing (MP). The surface roughness (Ra and Rz) was measured in a contact perfilometer and the flexural fatigue strength was evaluated by the step-test method (n = 20), using a piston-on-three ball assembly (ISO 6872:2008). A specific loading protocol, based on the results of a monotonic test (n = 5), was performed for each ceramic material. A maximum of 10,000 cycles was applied in each load step, at 1.4 Hz. Weibull probability statistics was used for the analysis of the fatigue flexural strength, and the non-parametric Mann-Whitney test (α = 0.05) was used to compare the roughness values (Ra and Rz) between M and MP groups for each ceramic material. M resulted in higher values of roughness and lower values of characteristic fatigue strength than MP. The greatest reduction in the characteristic fatigue strength from MP to M was observed in Y-TZP (40%; M = 536.48 MPa; MP = 894.50 MPa), followed by lithium disilicate (33%; M = 187.71 MPa; MP = 278.93 MPa) and leucite glass ceramic (29%; M = 72.61 MPa; MP = 102.55 MPa). Therefore, CAD/CAM machining affected negatively the flexural fatigue strength of ceramics with different microstructures. The results suggest that the machining of partially sintered materials may be as deleterious as the machining of fully sintered materials. Manuscript 2: Loading frequencies up to 20 Hz as an alternative to accelerate fatigue strength tests in a Y-TZP ceramic. This study aimed to investigate the influence of the loading frequency on the zirconia fatigue strength, by means of the staircase approach, at a maximum lifetime of 500.000 cycles, and using a piston-on-three ball assembly (ISO 6872:2008). The frequencies investigated were 2 Hz (control - simulation of the chewing activity; n = 20), 10 Hz (n = 20), 20 Hz (n = 20), and 40 Hz (n = 21). The fatigue strength data were analyzed using one-way ANOVA and post hoc Tukey`s test (α = 0.05). The fatigue strength was significantly higher for 40 Hz group (630.7 MPa) and did not differ among the groups 2 Hz (550.3 MPa), 10 Hz (574.0 MPa) and 20 Hz (605.1 MPa). Therefore, the use of loading frequencies up to 20 Hz seems a good alternative to expedite the cycling strength fatigue tests in polycrystalline ceramics.